PEMBERIAN KREDIT BANK DENGAN JAMINAN HAK GUNA BANGUNAN YANG JANGKA WAKTUNYA TELAH BERAKHIR SEDANGKAN PERJANJIAN KREDITNYA BELUM BERAKHIR - Etha Prianjaya, I Gede; R, Ibrahim; Westra, I Ketut (Acta Comitas : Jurnal Hukum Kenotariatan, 2017)
Bank is a financial institution that has an important role in the economy of a State based on the function of banks as a collector and distributor of public funds, as well as the types of products produced and supplied by the bank have become something significant and convenient enjoyed by people such as the provision of credit. Granting bank credit is stipulated in Law No. 7 of 1992 and its amendment, Law No. 10 of 1998 Article 6 letter b. Loans granted by banks contains a risk, so in practice the bank must pay attention to the principles of what healthy credit is. In order to reduce the risk, collateral for credit is an important factor considered by a bank. Title to a land that can be used as collateral, such as Building Rights stipulated in Article 35 of Law Number 5 of 1960 on Basic Regulation of Agrarian, as one of the land rights by law to have a controlling effect but with time its period must be expired. Expiration of Building Rights being used as a credit security encumbered encumbrance of course would have the legal effect of the existence of security rights itself. Based on that, it will cause problems as follows What is the position of  security building rights whose period has ended and the loan is not over and what is the efforts made by the bank to the credit agreement has not ended with the assurance that the right mortgage is over. This type of research used in this thesis is empirical legal research because there is a gap between the governing rules and the problems that occur in the community. Data collection techniques employed are interviews and document study techniques. For data analysis, descriptive analytical techniques are used, associated with the relevant theories and then summed to address the problems. The results of the study based on the problems addressed are: The position of the guarantee of building rights whose term has ended but the credit has not expired leads to the abolishment of building rights as land rights which still serve as credit guarantees. Efforts made by the bank to the credit agreement which has not ended are efforts to implement the binding power of attorney imposing liability rights during the extension process of building rights done in the office of the National Land Body.